(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to examine the level of knowledge, attitude, attitude and problem of teachers of Malay Language in implementing the classroom assessment (CA) for Malay Language subjects. CA is a holistic assessment, which assesses cognitive (intellectual), affective (emotional and spiritual) aspects and psychomotor (physical) in line with the Primary School Standard Curriculum and National Education Philosophy. A total of 95 Malay teachers in rural schools in Betong district, Sarawak were surveyed. The research instrument used is a questionnaire. The data were analyzed using Statistical Package for Social Science (SPSS) version 22. The data were analyzed using statistical and inferential statistics. The findings show that teachers are prepared to implement CA where the mean score of each element is high, that is, the knowledge of teachers (mean = 4.075), teacher skills (mean = 4.037) and teacher attitude (mean = 4.078). The implication of this study is that the teachers of Malay Language are ready to implement the CA although the implementation of the CA is a new one introduced by Ministry of Education.